A Provincial Residence at Bubastis from the 4ᵗʰ and 5ᵗʰ Dynasties and the Issue of the Administration of the Old Kingdom Nile Delta - Lange-Athinodorou, Eva (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
Excavations at Bubastis revealed evidence for the existence of a provincial residence of the 4ᵗʰ and 5ᵗʰ Dynasties, a time that is usually rather poorly represented in the provincial archaeological record, especially in the region of the Nile Delta. For the first time now, this new discovery opens up the possibility to investigate the role of local residences as drivers of the evolution of central places and key elements of provincial administration from the Early Dynastic Period until the late Old Kingdom in the Nile Delta. Especially intriguing is the question of the relation between provincial residences and provincial temples. The latter are acknowledged in scholarly research and literature as important institutions of the provincial administration for a long time, but they do not appear as such before the 5ᵗʰ Dynasty. Provincial residences, on the other hand, are attested already since the Early Dynastic Period. [...]